A comprehensive review on the spray cooling system employed to improve the summer thermal environment: Application efficiency, impact factors, and performance improvement. (1st June 2022) - Meng, Xi; Meng, Li; Gao, Yi; Li, Haoran
Abstract: The sustainable development and climate response have been paid attention to by many cities, especially under the high-temperature weather conditions in summer, which have caused huge environmental pressure on outdoor activities. The spray cooling system was the better choice to regulate the regional thermal environment in the outdoor high-temperature environment. This review focused on application efficiency, factors affecting cooling efficiency, optimization measures and future development of the spray cooling system, with the aims to provide a comprehensive and critical review of existing research and propose the future research trends. The results showed that the spray system could reduce the ambient temperature and improve the thermal comfort effectively, while the parameters of enhanced heat transfer were heavily discussed in the spray cooling system. The new thermal assessment models and extended parameters were also established to elevate the thermal comfort under the spraying environment. Finally, future directions were proposed on possible studies and applications. Graphical abstract: Image 1